Primary intraosseous carcinoma of mandible - Ankur Jethlia; Vaishali Keluskar; Arvind Shetti (Wolters Kluwer Medknow Publications, 2009)
Primary intraosseous carcinoma (PIOC) is a rare malignant neoplasm of the jaw which is locally aggressive with poor prognosis. These tumors are believed to arise from the odontogenic epithelium and hence are referred to as odontogenic carcinomas. Till date, 47 cases have been reported in the English literature. Herein, we report a case of PIOC of mandible in a 65-year-old male patient. This article discusses the importance of detailed clinical and histological examination and review of various aspects of PIOC and updates the literature.